Our earthquakes - Paula Viveros-Wacher; Arnoldo Kraus-Weisman (Instituto Nacional de Salud Pública, 2018)
September 2017 earthquake served us to reveal the face of society and the role of the State. The earthquake divided Mexico in two: one where citizens demonstrated their solidarity; and the other, an ineffective government which fell behind, displaced by the power and commitment of the people. Social structure allows people to create networks and share information that helps to manage and confront disasters. Social capital benefits are immense. Ours and previous experiences in earthquakes exalt the role of community and the transcendence of solidarity, empathy and of the commitment of those who exercise it.